Miss Spider's new car - Kirk, David (New York : Scholastic Press/Callaway, 1997)
Miss Sprider's and her husband go shopping for a car.
Keywords: Spiders-Fiction; Insects-Fiction; Automobiles-Fiction; Shopping-Fiction; Stories in rhyme